Transmission of Monetary Policy through Credit Interest Rates in Turkey: A Microeconomic Perspective - Siklar, Ilyas (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This study aims to examine the monetary policy transmission through the credit channel from a microeconomic perspective by using the fixed effect dynamic panel model. It is estimated to what extent policy interest rate changes are transferred to the short-term interest rate depending on the type of loan. Results confirm that there is a high degree of inertia in both the commercial and consumer loan interest rates. In terms of the transmission of monetary policy, changes in policy interest rates are transferred to commercial loan interest rates by 11% and consumer loan interest rates by 15% in the short term. These values reveal that policy interest rate changes are gradually transmitted to market interest rates. Variables representing bank size, leverage, and market power in terms of distinctive characteristics have a limited impact on both commercial and consumer loan interest rates in the analyzing period. However, the market share of a bank has a significant impact on both commercial and consumer loan rates.